Immunomodulator Intensification of Etioropic Therapy in Patients with Advanced Pulmonary Tuberculosis - V. M. Kolomiets; A. V. Abramov; N. V. Rachina; N. V. Rubleva (Антибиотики и Химиотерапия, 2020)
The study was aimed at possible increase of the therapy efficacy in patients with advanced tuberculosis by including immunomodulators to the treatment schemes. The data concerning 6034 patients with advanced tuberculosis, mainly fibrocavernous tuberculosis of the lungs, were analysed. Four groups of the patients were randomized. In group 1 the management of the patients included etiotropic therapy and some treatment and rehabilitation measures with the use of Cycloferon. The group 2 patients in addition to the etiotropic therapy and some treatment and rehabilitation measures were given Omega-3. In group 3 the management included the etiotropic therapy and some treatment and rehabilitation measures. In group 4 the etioropic therapy was used alone. The analysis showed that 3419 patients had primary pulmonary tuberculosis, 340 patients had relapsing tuberculosis and 2275 patients had long-term process. The etiotropic therapy efficacy was estimated after an intensive phase of not more than 3 months. In the cases with Mycobacterium tuberculosis drug resistance and some other unfavourable factors it was estimated after a 5-month intensive phase. The results confirmed that inclusion of immunomodulators to the treatment schemes allowed to increase the therapy efficacy and the patients' adherence to the treatment, as well as to shorten the period of the bacteria carriage. Thus, the use of Cycloferon in the schemes of the treatment of the patients with fibrocavernous pulmonary tuberculosis allowed to shorten the period of the pathogen carriage (as well as the drug resistant forms) in 94.1+3.33% of the patients in spite of concomitant diseases. The effect of Cycloferon in such cases was likely due to both its direct immunoprotective action and the improvement of the general state of the patients and their higher adherence to the treatment.